TAUTOS TAPATUMO BEIEŠKANT - Morkūnienė, Jūratė (Problemos, 2008)
Kuzmickas B. Tautos tapatumo savimonë: lietuvių savimonės bruožai. Monografija. Vilnius: MRU, 2007. 207 p. ISBN 978-9955-19-063-9 In Search of National Identity Jūratė Morkūnienė span>